Stylistics Comparison between MosibatNameh and Mantegh Al-teir of Attar and MasnaviManavi (Case Study: Poetry techniques) - Mostafa Mirdar Rezaei; SIAVASH HAGHJOU (مطالعات زبانی و بلاغی)
One of the benchmarks and tools for investigating the elements of the art is "stylistics", in which the study of literary instruments and rhetorical elements in the language of poets is one of the most accurate and metric methods for the understanding and drawing of poetic images. This quantitative-statistic based, first analyzes and compares two groups of single literary techniques (simile, poem, metaphor, metonymy, and amphibology) and combined Techniques (metonymy metaphor, metonymy amphibology metaphor, simile metonymy amphibology metaphor) in five hundred bits of two logical and ritualistic Masnavi (Mosibatnameh and Mantegh Al-teir) and then in the same amount of Rumi's MasnaviManavi and then analyzes them. The results of the research indicate the magnificent rhetoric of Mosibatnameh among the three Masnavi according to using the combined techniques. The amount of Rumi's usage of the single technique "metonymy" and "metaphorical" is so impressive that, taking into account the totality of dingle techniques, MasnaviManavi is better than the other two. But in the field of combined techniques, the MasnaviManavi has the lowest frequency, and it can be said that Rumi has little desire to take advantage of these techniques. However, in the combined section of single and combined techniques, it is considered to be at the higher level than the Mantegh Al-teir and at the lower level than Mosibatnameh. The Masnavi “Mantegh Al-Teir” in the single techniques section is the least-productive work and is lower than the other two works, and it is considered to be at the higher level than the MasnaviManavi and at the lower level than Mosibatnameh. But in the total number of single and combined techniques, it is lower than two other masnavi.